Burnout and satisfaction with life in teachers who conduct virtual classes in the context of a covid-19 pandemic - Celio Pillaca, José (2021)
The present study aimed to determine the relationship between the Burnout Syndrome and Satisfaction with Life in Regular Basic Education teachers who taught virtual classes during the COVID-19 pandemic in various departments of Peru. Under a quantitative methodology, with a descriptive-correlational design, the Maslach Burnout Inventory - Ed Form (MBI-Es) and the Satisfaction with Life Scale (SWLS) were applied virtually to 56 teachers, who were selected by sampling intentional non-probabilistic. The descriptive and inferential analysis of the data was carried out using the SPSS version 22 statistical program and it was found that the largest number of teachers feel very satisfied with life, have high levels of Emotional Exhaustion, low levels of Depersonalization and high levels of Achievement. Personal. Differences were found according to sex and workplace, and a statistically significant, low and positive relationship (p <.05, r = .323) was found between Personal Achievement and Satisfaction with Life.